The tip of an iceberg? Adult children’s experiences with parental suicidal behaviour in childhood - Geir Tarje Bruaset; Jennifer Drummond Johansen; Tine K. Grimholt (International Journal of Qualitative Studies on Health & Well-Being)
Purpose This study examined how children exposed to parental suicidal behaviour experienced their parents’ suicide attempts, their relationship with their parents, and family life from childhood to adult life. Methods This qualitative, exploratory study conducted semi-structured interviews with 11 participants recruited from next-of-kin organizations and social media. Open-ended interviews addressed childhood experiences, perceived difficulties, and helpful aspects. Interviews lasted approximately 70 minutes and were recorded and transcribed. Thematic analysis was utilized to analyse the data. Results We identified two main themes: an unstable, unpredictable upbringing environment and a lifelong responsibility. Participants did not regard their parent’s suicide attempt as the most traumatic event of their childhood. Instead, they identified parental instability due to serious mental illness and/or substance abuse as the most stressful factor. This instability imposed significant emotional and practical responsibilities on the children, forcing them to sacrifice their own development and sense of security. Responsibility was characterized as a life lasting burden. Conclusions Adult children of parents with suicidal behaviour reported that their parent’s mental illness was the most burdensome aspect of their upbringing, leading to an unstable home with significant responsibilities. These individuals require professional follow-up and should be offered individual counselling sessions as a clinical intervention.